Developing a Paradigm Model for Sports Marketing in Iranian Schools - Soroush Arianpour; Hadi Bagheri; Seyed Karim Saadat Mirghadim; Seyed Ehsan Hoseiny (Sports Business Journal)
Purpose: The current research aims to develop a model for sports marketing in Iranian schools using a foundational data approach.Methodology: Due to the exploratory nature of this research, a grounded theory method using a systematic approach was employed. Data were collected through semi-structured interviews, and the findings were assessed using conventional techniques to ensure their reliability. The participants in the study consisted of 13 experts who were purposively selected, including professors of sports management, members of the student sports federation, former heads of the General Department of Education, and sports teachers.Findings: The data analysis identified 94 concepts across 19 school sports marketing model categories. Three categories reflect contextual conditions: sports governance, institutional communication, and innovation. Causal conditions include economic stability, media management, and a knowledge-based economy. Intervening conditions involve cultural development and a resistance economy in schools. Six strategy categories were identified: event branding, stakeholder management, private sector collaboration, human resource training, agile marketing plans, and legal revisions. Finally, the five outcomes of the economic discourse model include promoting economic thinking in sports, developing educational sports, organizing equipment, monitoring performance, and enhancing talent management.Originality: The current research can use school sports to achieve marketing goals by designing a paradigmatic model for the development of sports marketing in Iranian schools.